Isolation of Human Eosinophils - Akuthota, Praveen (2012)
Highly purified eosinophils can be isolated from peripheral blood by negative selection using an antibody-based magnetic negative selection protocol. The basic protocol describes a sequential fractionation of peripheral blood in which CD16+ granulocytes are enriched first from whole blood, followed by isolation of eosinophils. This technique is easy to use, fast, and highly reproducible. Support protocols describe a staining methods that can be used to evaluate the purity of eosinophils and differentiation from other leukocyte populations.